FEATURES OF STATE SUPPORT FOR WOMEN'S ENTREPRENEURSHIP IN UZBEKISTAN - Mirzaeva Shakhnoza Shavkatovna (Western European Studies, 2024)
The article deals with the reforms carried out in Uzbekistan to improve the socioeconomic status and entrepreneurial activity of women, to provide them with training and employment in a profession, to involve them widely in entrepreneurship, and to provide social support to low-income groups of the population.
Keywords: Women entrepreneurs; financing; business initiatives; women's labor opportunities